Congenital syphilis. New questions about a neglected but re-emerging condition - Hernando Gaitán Duarte (Case Reports)
In this issue of Case Reports, Cifuentes-Cifuentes et al. (1) describe a case of congenital syphilis (CS) in a newborn resulting from the first pregnancy of a woman who, despite having been diagnosed with syphilis through serological tests four years earlier, had not received treatment.